Minimal phrases system for translating English to Spanish (Dissertare, 2021)
This article is the advance of a broader investigation, so its purpose is framed in presenting the progress of a translation system proposed to translate from English to Spanish applying minimal phrases. The research from which this work originates is of a qualitative type with emergent design and hermeneutical phenomenological method. The scope of study was the Dean of Sciences and Technology of the Universidad Centroccidental "Lisandro Alvarado" (UCLA, Venezuela). Observation and the self-administered survey were applied as information gathering techniques. In this sense, two English classes were observed on the content of the noun phrase, taught by different teachers. The survey was applied to 5 sections of students from the careers Computer Engineering, Systems Analysis, Production Engineering, Bachelor of Mathematics and Degree in Physics; from there, 5 questionnaires were selected. Triangulation was applied from the collected information contrasted with the theoretical references. So far, the analyzes have allowed the following interpretations to be made: a) teachers use the content of the noun phrase as the main element for teaching translation from English to Spanish; b) Students can recognize the nucleus in short noun phrases, however, when the phrase is accompanied by premodifiers and postmodifiers, it becomes confusing for the student.
Keywords: translation; noun phrase; minimal phrases; parts of speech